2017
DOI: 10.3390/epigenomes1030021
|View full text |Cite
|
Sign up to set email alerts
|

Switch-Like Roles for Polycomb Proteins from Neurodevelopment to Neurodegeneration

Abstract: Polycomb Group (PcG) proteins are best-known for maintaining repressive or active chromatin states that are passed on across multiple cell divisions, and thus sustain long-term memory of gene expression. PcG proteins engage different, partly gene-and/or stage-specific, mechanisms to mediate spatiotemporal gene expression during central nervous system development. In the course of this, PcG proteins bind to various cis-regulatory sequences (e.g., promoters, enhancers or silencers) and coordinate, as well the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
(154 reference statements)
1
6
0
Order By: Relevance
“…Specifically, while in normal B cells H3K27me3 hi /H3K4me3 low /H3K27ac low -marked genes were generally associated with a uniform transcriptional output, in CLL these genes were associated with variable expression level. As H3K27me3 is typically deposited at gene promoters by Polycomb Repressive Complex 2 (PRC2) via its catalytic Ezh2/Ezh1 subunit 34 , these results are consistent with CLL epigenetic landscape being marked by incomplete Polycomb complex-mediated gene silencing resulting in permissive chromatin states in a fraction of cells. Furthermore, as DNAme is important for appropriate retargeting of PRC2 and H3K27me3 histone modification across cell divisions 35 , stochastic DNAme alterations during CLL evolution 9 may lead to redistribution of the repressive activity of the PRC2 complex and the H3K27me3 mark, and cell-to-cell variation in the efficiency of PRC2 transcriptional silencing 36 .…”
Section: Discussionsupporting
confidence: 63%
“…Specifically, while in normal B cells H3K27me3 hi /H3K4me3 low /H3K27ac low -marked genes were generally associated with a uniform transcriptional output, in CLL these genes were associated with variable expression level. As H3K27me3 is typically deposited at gene promoters by Polycomb Repressive Complex 2 (PRC2) via its catalytic Ezh2/Ezh1 subunit 34 , these results are consistent with CLL epigenetic landscape being marked by incomplete Polycomb complex-mediated gene silencing resulting in permissive chromatin states in a fraction of cells. Furthermore, as DNAme is important for appropriate retargeting of PRC2 and H3K27me3 histone modification across cell divisions 35 , stochastic DNAme alterations during CLL evolution 9 may lead to redistribution of the repressive activity of the PRC2 complex and the H3K27me3 mark, and cell-to-cell variation in the efficiency of PRC2 transcriptional silencing 36 .…”
Section: Discussionsupporting
confidence: 63%
“…The remaining 50% are likely due to random fluctuation in epigenetic state present, even in distinct clones from the same iPSC line. Epigenetic variability detected within and across individuals reflects in part the activity of Polycomb proteins in agreement with their important role during (neuro) development [ 133 ]. In consequence, donor-specific variability can critically bias neuronal differentiation propensity independent of disease status in case/control studies ( Table 2 and Table 3 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent iPSC studies have therefore aimed to clarify to what degree variance across donors explains expression variation: Carcamo-Orrive [132] observed that ≈50% of genome wide expression variability in undifferentiated iPSCs (317 iPSCs from 101 healthy individuals) is explained by genetic variation across individuals. They also identified Polycomb targets to contribute significantly to the non-genetic variability seen within and across individuals [141]. By means of genome-wide profiling, Kilpinen et al [133] determined that 5–46% of the variation (variation median ≈6) in different iPSC phenotypes (711 iPSCs from 301 healthy individuals), including differentiation capacity and cellular morphology, arise from differences between individuals.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%